INDEKS HARGA SAHAM GABUNGAN DI TINJAU DARI SISI EKONOMI MAKRO PADA BEI - Novita Dwi Agustina; Yuniningsih Yuniningsih (Cakrawala Management Business Journal, 2020)
The purpose of this study was to determine the effect of inflation, SBI interest rates, and exchange rates on the Composite Stock Price Index (CSPI) and stock trading volume as interverning variables. Samples were taken by purposive sampling method, with sample selection criteria that is the closing price of JCI data (closing price), in the period January 2016 - October 2019 a number of 46 months. The type of data used in this study is secondary data. The analysis technique used is path analysis. The results of this study indicate that the research proves insignificant on CSPI. SBI interest rates have a significant negative effect on the CSPI. And the rupiah exchange rate is significantly positive for the CSPI. Also, the conversion to CSPI is different from the negative trading volume